Innate, T-, and B-Cell Responses in Acute Human Zika Patients. (17th August 2017) - Lai, Lilin; Rouphael, Nadine; Xu, Yongxian; Natrajan, Muktha S; Beck, Allison; Hart, Mari; Feldhammer, Matthew; Feldpausch, Amanda; Hill, Charles; Wu, Henry; Fairley, Jessica K; Lankford-Turner, Pamela; et al.
Abstract : Understanding the immune response during acute Zika in humans will aid vaccine design and testing. In 5 acute patients, including 2 pregnant women, viral levels and innate, T-, and B-cell responses against Zika or dengue viruses are described. Abstract: Background: There is an urgent need for studies of viral persistence and immunity during human Zika infections to inform planning and conduct of vaccine clinical trials. Methods: In 5 returned US travelers with acute symptomatic Zika infection, clinical features, viral RNA levels, and immune responses were characterized. Results: Two pregnant, flavivirus-experienced patients had viral RNA persist in plasma for >44 and >26 days. Three days after symptom onset, transient increases in proinflammatory monocytes began followed at 5 days by transient decreases in myeloid dendritic cells. Anti-Zika virus immunoglobulin M was detected at day 7 after symptom onset, persisted beyond 103 days, and remained equivocal through day 172. Zika virus–specific plasmablasts and neutralizing antibodies developed quickly; dengue virus–specific plasmablasts and neutralizing antibodies at high titers developed only in flavivirus-experienced patients. Zika virus– and dengue virus–specific memory B cells developed in both flavivirus-naive and -experienced patients. CD4+ T cells were moderately activated and produced antiviral cytokines after stimulation with Zika virus C, prM, E, and NS5 peptides in 4/4 patients. In contrast, CD8+ T cells were massively activated, but virus-specific cells that produced cytokines were present in only 2/4 patients assessed. Conclusions: Acute infections with Zika virus modulated antigen-presenting cell populations early. Flavivirus-experienced patients quickly recalled cross-reactive MBCs to secrete antibodies. Dengue virus–naive patients made little dengue-specific antibody but developed MBCs that cross-reacted against dengue virus. Zika virus–specific functional CD4+ T cells were readily detected, but few CD8+ T cells specific for the tested peptides were found.